Development of Lagrangian soot tracking method for the study of soot morphology in diesel spray combustion - Ong, Jiun Cai (2017)
The weakness of a conventional Eulerian soot model in capturing primary soot size and its inability to access individual soot information led to the development of a Lagrangian soot tracking (LST) model as reported in this thesis. The LST model aimed to access the history of individual soot particles and capture the soot concentration and primary soot size distribution in high pressure spray flames, under diesel-like conditions. The model was validated in a constant volume spray combustion chamber by comparing the predicted soot volume fraction (SVF), mean primary soot diameter and primary soot size distribution to the experimental data of n-heptane and n-dodecane spray combustion. The inception, surface growth and oxidation models were adopted and modified from the multistep Moss-Brookes (MB) soot model, which was used in this study as the representative of Eulerian soot model. Parametric studies were carried out to investigate the influence of soot surface ageing and oxidation rates on the overall soot formation. Following the parametric study, the developed LST model which incorporated surface ageing effect and higher oxidation rates was implemented to investigate the effect of ambient oxygen and density on soot morphology in n-heptane spray flame.